Outcomes of joint preservation surgery: comparison of patients with developmental dysplasia of the hip and femoroacetabular impingement - Belzile, Etienne L.; Beaulé, Paul E.; Ryu, Jae-Jin; Clohisy, John C. (Université d'Ottawa | University of Ottawa, 2016)
Femoroacetabular impingement (FAI) and developmental dysplasia of the hip (DDH) are fundamentally and structurally different hip abnormalities yet their clinical presentation can often be very similar. We asked whether adult patients surgically treated for DDH when compared with FAI patients achieve (i) better outcome as reflected by the WOMAC Osteoarthritis Index, (ii) higher physical activity as reflected by the UCLA physical activity scale. Five hundred fifty-six patients treated by periacetabular osteotomy for DDH and 540 patients treated for FAI (cam, pincer, or combined) in nine high-volume centers, between 2008 and 2011 were matched using propensity analysis, based on age and BMI. After exclusions, 144 pairs were evaluated on WOMAC, SF-12 Health Survey, modified Harris Hip Score (mHHS) and UCLA scale at pre and post-operations. At pre-operative evaluation, FAI patients showed lower scores on WOMAC (total, stiffness, function) and SF-12 physical. Statistically significant improvements in the outcome scores were observed from pre to post-operative time points in both treatment groups. Once FAI and DDH patients were compared, FAI patients showed lower scores on most of the outcome measures. However, these differences diminished in time, with only SF-12 mental and mHHS scores remaining significantly lower at 2-year follow-up. Because of more advanced disease at presentation, patients with FAI had an inferior clinical outcome compared with patients with DDH after surgical correction. Further prospective studies are required to better describe the long-term clinical benefits of hip joint preservation surgery.